PENGARUH GLOBALISASI EKONOMI, IPM, DAN POPULASI TERHADAP TINGKAT KEMISKINAN DI TUJUH NEGARA ANGGOTA OKI - Iqbal Firmani; Muhammad Tsanial Aif (Fakultas Ekonomi Universitas Pekalongan, 2021)
Poverty is a problem that is still an issue in almost all countries in the world, including countries that are members of the Organization of Islamic Cooperation (OIC). Based on data published by the World Bank, there are 7 OIC member countries that publish their national poverty data (during the study period), due to data limitations in this study using 7 OIC member countries as samples, these countries include: Indonesia, Turkey, Kazakhstan, Kyrgyzstan, Moldova, Tajikistan and Mali. The results of this study based on panel data regression testing using the Random Effect Model (REM) show that economic globalization is proxied by trade openness data and Foreign Direct Investments (FDI) has a significant positive effect on poverty in 7 OIC member countries, while the Human Development Index (HDI) ) has a significant negative effect on poverty. The population size variable does not have a significant effect on poverty in 7 OIC countries, this is in accordance with the probability of the t test which is above 5% alpha, which is 0.3563. Based on the interpretation of the data in this study, in order to overcome poverty, the most important thing is the development of human resources. With developed human resources, poverty in various countries, especially in OIC member countries, will be resolved.